PENATALAKSANAAN FISIOTERAPI PADA KONDISI TRIGGER FINGER DENGAN INTERVENSI ULTRASOUND (US), INFRARED (IRR) DAN TRANSVER FRICTION DI RSUD BENDAN KOTA PEKALONGAN - Swasta Raya Mantep Sasmito; Ade Irme Nahdliyyah (LPPM Universitas Pekalongan, 2013)
Trigger finger described as a condition in which the locking finger joints in motion at the time of the position fleksi to position ekstensi. This is because the inflamation local or a swelling of the tendon wrapping fleksor which resulted in wrapping it can not be normal to slide. Pathology changes in the triger finger commonly occurs as tendon inflammation flekxor digitorum profundus (stenosis), due to thickening of the tendon sheath stenosing tenosynovitis, this causes a decrease of capacity as a function of finger motion constraints, the presence of pain and muscle spasm and decreased functional ability is : writing disorders, lifting heavy objects. To provide efficient handling and effectiveness, then carried out an inspection method that measures the range of motion (LGS) with tools goneometer, muscle strength with Manual Muscle Testing (MMT), pain measurement with Verbal Descriptive Scale (VAS), functional disability with Durous Hand Index (DHI). After the action of physiotherapy during 6 time there is an increase in range of motion (LGS), decrease in pain with Verbal Descriptive Scale (VAS), increase in functional disability with Durous Hand Index (DHI). Keywords : Trigger finger, LGS, MMT, VAS, Durous Hand Index.